2012
DOI: 10.1016/j.ijhydene.2011.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of SOFC running on partially pre-reformed gas mixture

Abstract: A two dimensional model is developed to study the transport and reaction processes in solid oxide fuel cells (SOFCs) fueled by partially pre-reformed gas mixture, considering the direct internal reforming (DIR) of methane and water gas shift (WGS) reaction in the porous anode of SOFC.Electrochemical oxidations of H 2 and CO fuels are both considered. The model consists of an electrochemical, a chemical model, and a computational fluid dynamics (CFD) model. Two chemical models are compared to examine their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 35 publications
(43 reference statements)
0
64
0
Order By: Relevance
“…The electrochemical oxidation of methane (eqns (7)- (8)) is neglected, because the electrochemical oxidation rate of methane is neglible, compared to the ones for hydrogen and carbon monoxide [9,27]. Note that this electrochemical 13 approach also includes the gas-phase partial pressures, which are frequently neglected within the open literature and also in our previous models [3,37,44].…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical oxidation of methane (eqns (7)- (8)) is neglected, because the electrochemical oxidation rate of methane is neglible, compared to the ones for hydrogen and carbon monoxide [9,27]. Note that this electrochemical 13 approach also includes the gas-phase partial pressures, which are frequently neglected within the open literature and also in our previous models [3,37,44].…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
“…Also Ni [27] assumes the exchange current density for hydrogen electrochemical reaction to be 2.5 times that for the CO electrochemical oxidation. These assumptions can be compared to the result from Matsuzaki and Yasuda in [47], where it was concluded that the electrochemical oxidation rate of H 2 at the interface in a porous…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
“…Solid oxide fuel cells (SOFCs) offer the possibility of environmentally friendly production of electricity by high efficiency, low emissions of pollutants and several options of fuels [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…1). If hydrogen is used as fuel, the active species involved in the electrochemical reactions are oxygen and hydrogen, as shown in eqns (1)- (2). H 2 forms a molecule of H 2 O during this oxidation reaction and releases electrons [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their distinct features, extensive efforts have been made to develop efficient and reliable SOFCs systems capable of using various alternative fuels (i.e. conventional natural gas and renewable biofuel) for a variety of applications [6][7][8]. In order to improve the long-term stability of SOFC and decrease the cost of SOFC system, there is a trend to lower the operating temperature of SOFC [9].…”
mentioning
confidence: 99%